Perancangan Aplikasi Penjualan Furniture Dengan Metode Waterfall Berbasis Web - hendri hendri; Jefi Jefi; Desiana Nur Kholifah; Kusmayanti Solecha; Rio Nugraha Armanda (Computer Science (CO-SCIENCE), 2021)
Nowadays, technological advances are growing so rapidly, so that difficult jobs can be completed so easily. Many of the furniture shop owners want their shop to be widely known by the public, but the sales system used is still in manual form. By taking advantage of technological developments, furniture shop owners need a computerized system. Therefore, a web-based furniture sales application is needed. Making this program with the waterfall method. Making this application also uses the Codeigniter framework with the PHP programming language and MySQL database, which makes it easier for customers and shop owners to manage data, store information, process transactions and market furniture digitally.